Identification of the Similarities and Differences of Molecular Networks Associated With Fear Memory Formation, Extinction, and Updating in the Amygdala - Jinfeng Su (Frontiers Media S.A., 2021)
Abnormality of fear memory is one of the important pathogenic factors leading to post-traumatic stress disorder (PTSD), anxiety disorder, and other mental disorders. Clinically, although exposure therapy, which is based on the principle of fear memory extinction, has a certain effect on these diseases, it still relapses frequently in some cases. These troubles can be effectively solved by retrieving the memory in a certain time window before the extinction of fear memory. Therefore, it is generally believed that the extinction of fear memory is the result of forming new safe memory to competitively inhibit the original fear memory, while the retrieval-extinction operation is the updating or erasure of the original fear memory, thus, which has greater clinical therapeutic potential. However, what are the detailed molecular networks, specifically the circular RNAs (circRNAs), involved in fear memory updating, and the differences with fear extinction, are still unknown. In this study, we systematically observed the expression of mRNAs, microRNAs (miRNA), long non-coding RNAs (lncRNAs), and circRNAs in the basolateral amygdala of mice after fear memory formation, extinction, and updating by whole-transcriptional sequencing, then a variety of inter-group comparison and bioinformatics analysis were used to find the differential expressed RNAs, enrich the function of them, and construct the molecular interaction networks. Moreover, competing endogenous RNA (ceRNA) molecular networks and transcriptional regulatory networks for the candidate circRNAs were constructed. Through these analyses, we found that about 10% of molecules were both involved in the fear memory extinction and formation, but the molecules and their signaling pathways were almost completely different between fear memory extinction and updating. This study describes a relatively detailed molecular network for fear memory updating, which might provide some novel directions for further mechanism research, and help to develop a specific physical method for fear memory intervention, based on the regulation of these key molecules.